2019
DOI: 10.1155/2019/2536781
|View full text |Cite
|
Sign up to set email alerts
|

Arginase-1 and Treg Profile Appear to Modulate Inflammatory Process in Patients with Chronic Gastritis: IL-33 May Be the Alarm Cytokine in H. pylori-Positive Patients

Abstract: Helicobacter pylori (H. pylori) is a highly prevalent bacterium in our environment, directly involved in various upper digestive tract diseases, such as gastritis, peptic ulcer, and gastric cancer. Several molecules activating the immune system have been reported to be involved in containing H. pylori infection. This study is aimed at analyzing the mRNA expression of the cytokines IFN-γ, IL-17, IL-10, TGF-β, IL-6, IL-22, IL-23, and IL-33; transcription factors T-bet, RORC, and FOXP3; enzymes ARG1, ARG2, and NO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“… 18 However, it differed from the study of Da Silva et al. 25 Their findings showed that there were no significant differences in the expression of IL10 among chronic active gastritis patients, chronic inactive gastritis patients, or control cases, but the expression of FOXP3 in H. pylori -infected patients was significantly lower than that in non-infected patients. This discrepancy may be the reason that Treg cells are associated with VacA alleles, virulence factor and oipA status of H. pylori and histological grade.…”
Section: Discussionmentioning
confidence: 65%
“… 18 However, it differed from the study of Da Silva et al. 25 Their findings showed that there were no significant differences in the expression of IL10 among chronic active gastritis patients, chronic inactive gastritis patients, or control cases, but the expression of FOXP3 in H. pylori -infected patients was significantly lower than that in non-infected patients. This discrepancy may be the reason that Treg cells are associated with VacA alleles, virulence factor and oipA status of H. pylori and histological grade.…”
Section: Discussionmentioning
confidence: 65%
“…Restoration of GST-α level by AP39 confirmed our previous observation on ischemia/reperfusion-induced gastric injury [ 30 ]. ARG1 was shown to be upregulated in gastric mucosa of patients with inactive gastritis [ 86 ]. However, increased activity of ARG1 decreases l -arginine level.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have suggested that IL-33 may be an alarmin in H. pylori -positive patients ( 135 ). IL-33 is highly expressed in the mucosa of patients with H. pylori -infected gastritis ( 136 ), and ST2 is recruited into membrane rafts in response to IL-33 release by H. pylori -infected gastric epithelial cells ( 137 ), which promotes the production of tumor necrosis factor-α (TNF-α) by MCs and inhibits the proliferation of gastric epithelial cells, leading to the progression of H. pylori -associated gastritis and bacterial colonization ( 138 ).…”
Section: Gastric Alarmin Nuclear Binding Proteins: Il-33 and Hmgb1mentioning
confidence: 99%